A mechanistic study of the tremor associated with epidural anaesthesia for intrapartum caesarean delivery. (August 2020) - Mullington, C.J.; Low, D.A.; Strutton, P.H.; Malhotra, S.
Highlights: The mechanism underlying epidural top-up tremor was investigated. Tremor, EMG and body temperature (actual and sensed) were recorded. Obstetric patients and non-pregnant females were compared. Epidural top-up tremor is a form of non-thermoregulatory shivering. The tremor trigger is likely a reduction in sensed body temperature. Abstract: Background: It is not known if the tremor associated with an epidural top-up dose for intrapartum caesarean delivery is thermoregulatory shivering. A tremor is only shivering if it has the same frequency profile as cold stress-induced shivering. Thermoregulatory shivering is a response to a reduction in actual body temperature, whereas non-thermoregulatory shivering may be triggered by a reduction in sensed body temperature. This mechanistic study aimed to compare: 1. the frequency profiles of epidural top-up tremor and cold stress-induced shivering; and 2. body temperature (actual and sensed) before epidural top-up and at the onset of tremor. Methods: Twenty obstetric patients received an epidural top-up for intrapartum caesarean delivery and 20 non-pregnant female volunteers underwent a cold stress. Tremor, surface electromyography, core temperature, skin temperature (seven sites) and temperature sensation votes (a bipolar visual analog score ranging from −50 to +50 mm) were recorded. Results: The mean (SD) primary oscillation (9.9 (1.9) Hz) frequency of epidural top-up tremor did not differ from that of cold stress-induced shivering (9.0 (1.6) Hz; P =0.194), but the mean (SD) burst frequency was slower (6.1 (1.2) × 10 −2 Hz vs 6.9 (0.7) × 10 −2 Hz, respectively; P =0.046). Before the epidural top-up dose, the mean (SD) core temperature was 37.6 (0.6) °C. Between the epidural top-up dose and the onset of tremor the mean (SD) core temperature did not change (–0.1 (0.1) °C; P =0.126), the mean (SD) skin temperature increased (+0.4 (0.4) °C; P =0.002) and the mean (SD) temperature sensation votes decreased (−12 (16) mm; P =0.012). Conclusion: These results suggest that epidural top-up tremor is a form of non-thermoregulatory shivering triggered by a reduction in sensed body temperature.